Regional Impact of Bioenergy Development (Biomass) in Argentina. An Input-Output Analysis for the Province of Misiones - Perrotta, Lorenzo (Ediciones UNL. Secretaría de Extensión de la UNL, 2021)
Since current patterns of energy consumption and production are severely stressing natural and social systems, it is necessary not only to improve energy efficiency but also to produce energy in an environmentally sustainable way. In this context, the use of biomass as a renewable source of energy generation could allow clean energy production, particularly in regions where there is a natural comparative advantage and where the access to other sources of energy is expensive. This is the case of Misiones, a province in Argentina, which displays a high potentialfor energy production through biomass from its forestry activity. The main objective of this paper is to evaluate the net social benefit of the development and the investment (technology, infrastructure, etc.) in bioenergy from biomass in this province. For this evaluation, a regional input-output model for Misiones has been developed. It allows the analysis of the impact of different scenarios on the level of employment and provincial production to be carried out. Three scenarios have been simulated: one in which energy production is increased, another one in which the existing production capacity is expanded through investments and, finally, the production and investment costs needed to expand production to potential levels are valued. Results have shown a great impact on both production and job creation in all the scenarios, reaching the greatest level of impact in those scenarios in which investments are made with local components, managing to capture the positive effects within the province. The conclusions provide some policy recommendations for boosting the development of biomass as a source for energy generation in Argentina since current regulations and programs in the sector are not regionally oriented.